Methodology Forming The Concepts Of Astronomy And Cosmonautics In Initial Classes - Kahor Tursunov, Ergash Makhmanov (International Journal of Advanced Science and Technology, 2020)
In the article, a scientific understanding of the astronomical picture of the world should be formed gradually. It is necessary to prepare children and adolescents for a long time and patiently for a meaningful perception of the grandiose space-time scales inherent in the astronomical picture of the world.